4(u-7)-6u=-12

Simple and best practice solution for 4(u-7)-6u=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(u-7)-6u=-12 equation:



4(u-7)-6u=-12
We move all terms to the left:
4(u-7)-6u-(-12)=0
We add all the numbers together, and all the variables
-6u+4(u-7)+12=0
We multiply parentheses
-6u+4u-28+12=0
We add all the numbers together, and all the variables
-2u-16=0
We move all terms containing u to the left, all other terms to the right
-2u=16
u=16/-2
u=-8

See similar equations:

| 10^2*3^2=s^2 | | 48=-1.9f-(-48.95) | | 4.9t^2+3t-950=0 | | 32​ x2−21​ x−43​ =0 | | -8x+19x=25+8 | | -28=2u-48 | | 18^2+18^2=x^2 | | 2u3u=45 | | 7/4=n/2 | | 30/0.5=y/0.52 | | 35=5x-8 | | x-0.15x=66 | | (10x-2)=7x | | 84=6x-6 | | 1/6x-19=1/2 | | a^2+8^2=15^2 | | 1/6x-19=1/2(8)*4 | | -22-9c=2c | | a^2+8=14 | | 3(2m+4)=36 | | 25=3v-7v | | -1.4m=2.8 | | 6084=c^2 | | 3b+4=4b-5 | | E=-2p+160 | | -4t=-48 | | -5a-2+4a=-28 | | -28-5h=-4(3h-7) | | 50÷5+3∙4÷2-1=x | | C(x)=40.25-0.05 | | 4x+3x-4=34 | | 2x+-3x+5=6 |

Equations solver categories